Poorly Differentiated Neuroendocrine Tumor of the Bladder: A Case Report - Singh, Dr. Hanuwant; Thakkar, Dr. Konark; Gheewala, Dr. Panth; Gupta, Dr. Kavita (International Journal of Medical Science and Clinical Research Studies, 2023)
Neuroendocrine tumors rarely occur in the urinary bladder, relatively less than 1% of occurrence, as the tumor is very rare, pathogenesis is uncertain some authors showed that it is from urothelial origin. It can be carcinomatous, subdivided into small cell and large cell pathology. Small cell carcinoma of the bladder is a rarity that may present at an advanced pathologic stage. No treatment regimens have been standardized for local or metastatic disease. Many publications showed that the disease is treated with combined chemotherapy or with radical cystectomy, here we are presenting a case of a 78 years old male, who underwent transurethral resection of bladder 1 month ago and the biopsy report was suggestive of neuroendocrine tumor of bladder, after that patient underwent radical cystectomy with neobladder reconstruction surgery.